Self-Assembly in the Design of Cooperative Catalysts for Organic Synthesis - Solís Muñana, Pablo (Auckland University of Technology, 2021)
Catalysis is, without a doubt, one of the most powerful approaches for accelerating chemical reactions and the facilitation of new reaction pathways. Recently, catalyst systems that involve the active participation of multiple catalytic units have generated intense interest among chemists due to improved efficiencies and access to novel reactivities. Examples of catalysts that utilise multiple, simultaneous activation sites include enzymes, which in general can catalyse reactions with much higher efficiencies than synthetic catalysts. Furthermore, for reactions involving multiple catalytic units, their efficiency can be improved when the required catalytic units are brought together into proximity. The direct covalent linking of catalytic units is the most common strategy to bring requisite catalytic units together. While this approach can be used to produce well-defined catalytic pockets, it also presents inconveniences from a synthetic point of view, and its non-modularity can complicate the optimisation of the catalyst. In this thesis, an alternative, modular approach for bringing catalyst units into proximity is presented, based on the introduction of hydrophobic interactions to induce self-assembly. In a proof-of-concept study, we synthesised amphiphilic catalysts containing the Zn2+-binding ligand 1,4,7-triazacyclononane attached to a C16-hydrocarbon chain (C16TACN). This amphiphilic ligand self-assembled in aqueous buffer to form vesicular structures, allowing the formation of catalytic pockets that catalysed the transphosphorylation of hydroxypropyl p-nitrophenyl phosphate (HPNPP). We demonstrated that our vesicular system could accelerate the reaction three orders of magnitude faster than the control molecule and that this rate acceleration could be attributed to the ability of neighbouring catalytic units to act cooperatively. Remarkably, the formation of the assembled catalyst was observed to be promoted by the presence of the HPNPP substrate, in analogy to many natural systems. To demonstrate that introduction of hydrophobic interactions could be advantageous for the design of catalysts for synthetically useful reactions, we applied these concepts to a catalyst designed for the hydrolytic kinetic resolution (HKR) of terminal epoxides. Jacobsen’s HKR of epoxides requires the simultaneous interaction of two catalytic units in the transition state of the rate-determining step, and thus benefits from preorganisation that brings the catalyst units together. We designed a (salen)Co complex functionalised with hydrocarbon chains to increase its hydrophobicity and its propensity to self-assemble. We demonstrated that our functionalised catalyst could perform the HKR 10 times faster than the commercially available complex. This is due to two effects: enhanced cooperativity due to self-assembly in homogenous conditions, and increased homogenisation between the phases under biphasic conditions. The novel complex can be utilised in industrially relevant neat conditions, without the addition of organic solvents.
Keywords: Cooperative Catalysis; Organic Chemistry; Supramolecular Chemistry; Systems Chemistry